Model integration for assessing future hydroclimate impacts on water resources, agricultural production and environmental quality in the San Joaquin Basin, California - Trevelyan Quinn, Nigel William (2004)
The US National Assessment of the Potential Consequences of Climate Variability and Change provides compelling arguments for action and adaptive measures to help mitigate water resource, agricultural production and environmental quality impacts of future climate change. National resource planning at this scale can benefit by the development of integrated impact analysis toolboxes that allow linkage and integration of hydroclimate models, surface and groundwater hydrologic models, economic and environmental impact models and techniques for social impact assessment. Simulation models used in an assessment of climate change impacts on water resources, agriculture and environmental quality in the San Joaquin Basin of California are described in this paper as well as the challenges faced in linking the component models within an impacts assessment toolbox. Results from simulations performed with several of the tools in the impacts assessment toolbox are presented and discussed. After initially attempting model integration with the public domain, GIS-based modeling framework Modular Modeling System/Object User Interface (MMS/OUI), frustration with the framework’s lack of flexibility to handle monthly timestep models prompted development of a common geodatabase to allow linkage of model input and output for the linked simulation models. A GIS-based data browser was also developed that works with both network flow models and makes calls to a model post-processor that shows model output for each selected node in each model network. This data and output browser system is flexible and can readily accommodate future changes in the model network configuration and in the model database.